An analysis of mathematical representation ability middle school students on concept congruence on learning style - Imama, Khoirunnisa; Caswita, Caswita (Universitas Islam Raden Intan Lampung, INDONESIA, 2023)
The ability of mathematical representation helps students solve mathematical problems in forms that are easy to understand and more concrete, so that they can maximize their potential for achievement in learning mathematics. The purpose of this study was to describe the mathematical representation abilities of junior high school students on the concept of congruence in terms of learning styles. The subjects of this study were 35 grade VIII junior high school students using a random sampling technique. Data collection was carried out using mathematical representation ability tests, learning style questionnaires, and interviews. After that, it was analyzed using triangulation techniques to determine the validity of the data. The results showed that on average, students have very good visual representation abilities with auditory, visual, and kinesthetic learning styles because all students can solve questions correctly according to the indicators. Students who have the ability to represent good expressions or equations have a visual learning style. Whereas students with word representation abilities cannot be said to be good because of the existing subjects, there are no students with any learning style who can solve word representation ability questions correctly. Based on this, it can be concluded that the low representation ability of students is not influenced by their learning styles, both visual, auditory, and kinesthetic, especially in the concept of congruence.